2017
DOI: 10.1107/s2053230x17004964
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the RNA 2′,3′-cyclic phosphodiesterase fromDeinococcus radiodurans

Abstract: 2',3'-Cyclic phosphodiesterase (CPDase) homologues have been found in all domains of life and are involved in diverse RNA and nucleotide metabolisms. The CPDase from Deinococcus radiodurans was crystallized and the crystals diffracted to 1.6 Å resolution, which is the highest resolution currently known for a CPDase structure. Structural comparisons revealed that the enzyme is in an open conformation in the absence of substrate. Nevertheless, the active site is well formed, and the representative motifs interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…to high-dose IR or toxic concentrations of mitomycin C. Along the same lines, Han et al (35) recently reported that another putative Deinococcus RNA end-processing enzyme, DR_2239, plays an important role in resistance to nucleic acid damage. The DR_2239 gene, which is strongly transcriptionally upregulated during recovery from IR (25,26), encodes a member of the 2H phosphoesterase enzyme superfamily (36). Disruption of the DR_2239 gene renders Deinococcus 5-fold more sensitive to 10 kGy of IR exposure but 2,000-fold more sensitive to treatment with 40 g/ml mitomycin C vis à vis the wild-type strain (35).…”
Section: Discussionmentioning
confidence: 99%
“…to high-dose IR or toxic concentrations of mitomycin C. Along the same lines, Han et al (35) recently reported that another putative Deinococcus RNA end-processing enzyme, DR_2239, plays an important role in resistance to nucleic acid damage. The DR_2239 gene, which is strongly transcriptionally upregulated during recovery from IR (25,26), encodes a member of the 2H phosphoesterase enzyme superfamily (36). Disruption of the DR_2239 gene renders Deinococcus 5-fold more sensitive to 10 kGy of IR exposure but 2,000-fold more sensitive to treatment with 40 g/ml mitomycin C vis à vis the wild-type strain (35).…”
Section: Discussionmentioning
confidence: 99%